2003
DOI: 10.1038/sj.onc.1206540
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide-mediated clustering is required for CD95-DISC formation

Abstract: Early events required for induction of apoptosis by CD95 are preassociation of CD95, the formation of the deathinducing signaling complex (DISC) and clustering of CD95 in distinct membrane domains. Here, we identify the molecular ordering of these events and show that the acid sphingomyelinase (ASM) functions upstream of the DISC to mediate CD95 clustering in ceramide-enriched membrane platforms, an event that is required for DISC formation. Experiments in ASM-deficient cells revealed that CD95 ligation, in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
231
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 255 publications
(251 citation statements)
references
References 44 publications
15
231
5
Order By: Relevance
“…Instead, receptor O-glycosylation appeared to be required for efficient ligand-induced clustering of DR4 and DR5, which triggers DISC assembly and caspase-8 activation. Clustering of the Fas receptor has been shown to depend on the generation of ceramide-enriched membrane microdomains by acid sphyngomyelinase (Grassme et al, 2001(Grassme et al, , 2003. Similarly, several studies have suggested a role of ceramide-rich platforms in signaling Apoptosis signaling by Apo2L/TRAIL F Gonzalvez and A Ashkenazi by DR4 and DR5 (Martin et al, 2005;Dumitru et al, 2007).…”
Section: Recent Advances In Understanding Apoptosis Initiationmentioning
confidence: 98%
“…Instead, receptor O-glycosylation appeared to be required for efficient ligand-induced clustering of DR4 and DR5, which triggers DISC assembly and caspase-8 activation. Clustering of the Fas receptor has been shown to depend on the generation of ceramide-enriched membrane microdomains by acid sphyngomyelinase (Grassme et al, 2001(Grassme et al, , 2003. Similarly, several studies have suggested a role of ceramide-rich platforms in signaling Apoptosis signaling by Apo2L/TRAIL F Gonzalvez and A Ashkenazi by DR4 and DR5 (Martin et al, 2005;Dumitru et al, 2007).…”
Section: Recent Advances In Understanding Apoptosis Initiationmentioning
confidence: 98%
“…We suggested that ceramide-enriched membrane domains serve to re-organize receptor molecules and intracellular signaling molecules in the cell membane [51], which permits the specific receptor to transmit its signal into the cell. Ceramide-enriched membrane domains exhibit very different biophysical properties than other parts of the plasma membrane resulting in preferential trapping of activated receptor molecules and/or signaling molecules in these domains.…”
Section: Ceramidementioning
confidence: 99%
“…Autocatalytic activation of pro-caspase 8 can lead directly to the proteolytic activation of pro-caspase 3, and the rapid initiation of DNA fragmentation (the so called extrinsic pathway), or it can lead to the initiation of mitochondrial membrane transition through the insertion of t-Bax into the mitochondrial membrane (the intrinsic pathway), formation of the apoptosome and slower activation of pro-caspase 3 and DNA fragmentation. Although it is not yet established what leads to the choice of which pathway is selected after assembly of the DISC, it has been suggested that it may be related to the amount of pro-caspase 8 recruited to the DISC which in turn may be dictated by other components required for the assembly of the DISC such as acid sphingomyelinase, 21 selective recruitment of the inhibitor cFLIP to the DISC, 22,23 or more fundamental changes in the biosynthesis and surface expression of specific death receptors. 24 Activation of caspase 8 is necessary but not sufficient for the induction of cell death, inhibition of the receptor tyrosine kinase mediated cell survival pathways is also necessary to ensure that cells complete the apoptotic process.…”
Section: On the Trail Of Cell Death Pathways In Prostate Cancermentioning
confidence: 99%